A NORTHERN RECORD OF PANTROPICAL SPOTTED DOLPHINS (Stenella attenuata) IN SOUTHWEST ATLANTIC OCEAN - Gurjao, Livio (Arquivos de Ciências do Mar, 2020)
Pantropical spotted dolphins, Stenella attenuata, are found across all tropical and subtropical oceans around the world, but their distribution is poorly known in the Southwestern Atlantic Ocean (SWA). A group of approximately 10 S. attenuata individuals was sighted in deep (~3,000 m), warm (~27.5 °C) and oligotrophic waters, near oceanic banks off northeastern Brazil (02°04’16.68” S and 038°08’28.26” W). This sighting constitute a new record of the northern distribution of S. attenuata in SWA. More survey efforts must be carried out to investigate cetaceans distribution along the Brazilian coast, especially in offshore waters.